PELVIC FLOOR RECONSTRUCTION WITH GLUTEUS MAXIMUS FLAP AFTER EXTRALEVATOR ABDOMINOPERINEAL EXCISION OF THE RECTUM - V. S. Belyaev; A. A. Nesytyh; Y. A. Dykhno; A. A. Versenyov; I. A. Laletin; Y. A. Kozina (Сибирский онкологический журнал, 2018)
Background. Rectal cancer is one of the most common malignancies worldwide. The incidence and mortality rates of rectal cancer are increasing rapidly, particularly in countries with a high-income economy. Surgery is the main treatment for rectum cancer. About 30 % of rectal cancer patients are eligible for abdominoperitoneal excision (APE) of the rectum. The conventional APE is characterized by a high frequency of local recurrences. T. Holm (2007) offered to perform extralevator abdominoperineal excision (ELAPE) of the rectum as a more radical approach than conventional APE for patients with cancer of the rectal ampulla and anal canal. Description. We present two case reports of locally advanced cancer of the anal canal. The patients underwent ELAPE with gluteus maximus flap reconstruction of the pelvic floor. Conclusion. The use of the gluteus maximus flap allows successful closure of the extensive peritoneal defect resulted from extralevator abdominoperineal excision of the rectum, without severe functional disorders of the lower extremities.